Avaliação do efeito de diferentes parâmetros de usinagem sobre os desvios dimensional e geométrico no torneamento de uma liga de titânio - Marques, Douglas Luis (Universidade Federal de São Carlos, 2023)
Titanium alloys are of great importance as biomaterials due to their high corrosion resistance and biocompatibility. Titanium has a low elasticity modulus when compared to steel alloys of similar mechanical resistance, furthermore it has a relatively low thermal conductivity the makes heat dissipation more difficult, which results in complex dynamics during its machining. The choice of machining parameters must have this behavior in focus, since it affects the tools' structural integrity and lifespan and may precarize the machined surface. The current work has determined the influence of varying axial depth of cut, cutting speed and feed rate on roundness deviation and dimensional deviation when machining 9 Ti-6Al-4V titanium alloy parts using the Taguchi L9 method. It was determined that none of the properties had any significant variable. For the dimensional deviation, despite the absence of a significant variable, it was clear the effect of the variation of each parameter, which tended to reduce the difference between the effective and the nominal diameter while they increased, with the exception of the cutting speed. For circularity deviation, although no significant variable was determined, Taguchi's method allowed the visualization of the increasing effect on deviation of the feed and depth of cut parameters, while cutting speed had a decreasing effect on the amplitude of peaks, valleys and overall circularity in the parts. The measured values of circularity kept inside the expected limits for the turning process, but the dimensional deviation went beyond what was expect, being nearly double the value that was established as tolerance for the turning process. The search for significant variables was shown to be inconclusive but it was possible to observe how the different values of the parameters affected the final result, allowing one to to choose the parameters in a way that they fit better with the wished final results.
Evaluation of the effect of different machining parameters over dimensional and geometric deviations on titanium alloy turning
Keywords: Biomateriais; Tolerâncias dimensionais; Tolerâncias geométricas; Dinâmica de usinagem; Circularidade; Biomaterials; Dimensional tolerances; Geometric tolerances; Machining dynamics; Circularity; ENGENHARIAS::ENGENHARIA MECANICA